2019
DOI: 10.1177/0969733018814902
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress in undergraduate nursing students

Abstract: Background: Moral distress is considered to be the negative feelings that arise when one knows the morally correct response to a situation but cannot act because of institutional or hierarchal constraints. Objectives: To analyze moral distress and its relation with sociodemographic and academic variables in undergraduate students from different universities in Brazil. Method: Quantitative study with a cross-sectional design. Data were collected through the Moral Distress Scale for Nursing Students, with 499 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 20 publications
2
27
0
7
Order By: Relevance
“…is finding is consistent with the results of Bordignon et al, Baghdadi et al,and Kamali [19,24,37]. However, some studies have indicated no significant relationship between work experience and MD [22,26].…”
Section: Phrasessupporting
confidence: 93%
See 2 more Smart Citations
“…is finding is consistent with the results of Bordignon et al, Baghdadi et al,and Kamali [19,24,37]. However, some studies have indicated no significant relationship between work experience and MD [22,26].…”
Section: Phrasessupporting
confidence: 93%
“…Moreover, it might generate some indifference and pessimism about nurses and decrease interests in nursing [14][15][16][17][18][19][20][21][22][23]. Regarding MD, several studies have been performed on nurses and nursing students, accompanied by different results [3,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,19 Moreover, the students interviewed reported difficulties in following practices and rules that are not in line with their own values. 16,31 This internal conflict, leading to a decline in wellbeing, is known in literature as moral distress and it affects many healthcare professionals, particularly so when dealing with bioethical and moral issues. 1,2,32 In this regard, senior clinicians may support the medical students towards the understanding and the adoption of a taking care approach in accordance with local habits and customs, to adequately take care of their patients and caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…17 The development of moral sensitivity and consequent dealing with ethical problems, however, may be weakened in the different care settings because the teaching of ethics is fragmented and out of context, while the working hours available to address this subject in most undergraduate nursing programs is insuficient. 18 In this sense, a study intending to identify the perception of students in regard to their professional preparedness highlights the importance of students in showing interest to filling in gaps in their education, especially through extracurricular activities so they may more fully visualize that reality is full of conflicts that are seldom addressed in classes or even during practical activities. 19 Additionally, there is a need to promote in future nursing workers their ability to deal with ethical conflicts in their inter-relationships with the team, between patients and nurses, so they can act in a morally mature manner, which is a process that leads to moral sensitivity.…”
Section: Discussionmentioning
confidence: 99%